1972
DOI: 10.1136/bmj.1.5797.406
|View full text |Cite
|
Sign up to set email alerts
|

Sebum Excretion in Acromegaly

Abstract: SummaryThe sebum excretion rate (S.E.R.) was measured in 20 patients with acromegaly. Eleven were untreated at the time of the measurement and nine had previously undergone surgical hypophysectomy or had received pituitary irradiationby yttrium-90 or radiotherapy. In five patients the S.E.R. was measured before and after such treatment. The mean S.E.R. in the untreated acromegalics was much greater than in a normal population and decreased significantly after successful pituitary ablation. No significant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…On the other hand, the increased serum GH levels in acromegaly has been associated with enhanced sebum secretion (Burton et al, 1972) an observation that could be confirmed by GH…”
Section: Growth Factorsmentioning
confidence: 81%
“…On the other hand, the increased serum GH levels in acromegaly has been associated with enhanced sebum secretion (Burton et al, 1972) an observation that could be confirmed by GH…”
Section: Growth Factorsmentioning
confidence: 81%
“…Growth hormone (GH) activity is considered to be mainly attributed to IGF but GH has also been shown to exhibit direct effects on human skin cells. 44 The increased serum GH levels in acromegaly are associated with enhanced sebum secretion, 45 an observation that could be confirmed by GH treatment of human SZ95 sebocytes in vitro. 46 In acne vulgaris, increased sebum production peaks in mid-adolescence at a time that GH and IGF-I reach their highest serum levels.…”
Section: 21mentioning
confidence: 87%
“…The increased serum GH levels in acromegaly are associated with enhanced sebum secretion [48], an observation that could be confirmed by GH treatment of human sebocytes in vitro [49]. In acne vulgaris, increased sebum production peaks in mid-adolescence at a time that GH and IGF-I reach their highest serum levels [50].…”
Section: Ghmentioning
confidence: 86%